Optical Pdms Microfibre Sensor For Displacement Determination - Daniel Kacik; Ivan Martincek; Norbert Tarjanyi (Communications - Scientific letters of the University of Zilina, 2017)
We prepared and demonstrated the usage of an optical polydimethylsiloxane (PDMS) microfibre sensor for displacement measurement. The sensor consists of PDMS microfibre placed between two conventional single-mode optical fibres. For proper bend of the microfibre the structure forms Mach-Zehnder interferometer. In that case, one arm of the interferometer consists of the microfibre and second one of the air. In addition, it is possible to resize the air arm in a range of several tens of micrometres with sufficient ratio of intensities between lights transmitted through the interferometer arms. For optical paths difference smaller than optical coherence of light source one can observe the interference of light. Determination of the displacement was done based on the spectral shift of interference pattern for particular lengths of air arm. The sensitivity of the sensor was 2.5 nm/μm.